Combustion mechanism and CFD investigation of methyl isobutanoate as a component of biodiesel surrogate. (15th June 2022) - Lin, Kuang C.; Dahiya, Anurag; Tao, Hairong; Kao, Fan-Hsu
Abstract: Branched-chain fatty acid methyl esters (FAME), known for cold flow improvers for biodiesel, have received less attention to their chemical kinetics in flames. This study proposes a detailed mechanism reduced to be a compact form to predict the formation of non-fuel small hydrocarbons and light-weight polycyclic aromatic hydrocarbons (PAH) from the oxidation of methyl isobutanoate [MIB, (CH3 )2 CHC(=O)OCH3 ], a C5-branched methyl ester. Using the path flux analysis, the newly constructed MIB oxidation mechanism with 344 species and 2147 reactions is shrunk and refined to 63 species and 288 reactions, a minimum size for its application to computational fluid dynamics. The minimized MIB mechanism incorporated into a 2D axisymmetric coflow model is used to validate mass-spectrometric data obtained from a laminar coflow diffusion flame of methane doped with MIB. For the first time, ten experimentally measured centerline profiles in the flame are computationally interpreted by nine C3–C6 unsaturated hydrocarbons, three carbonyls and four aromatics. Furthermore, we analyze the spatial distribution of the investigated intermediates and reveal their corresponding reaction pathways linked to the MIB decomposition. Highlights: Compact kinetic mechanism for methyl isobutanote oxidation is proposed. CFD coupled with the kinetic mechanism describes chemistry in a nonpremixed flame. Non-fuel hydrocarbons measured by mass-spectrometry are modeled for the first time. Reaction pathway analyses elucidate abundant formation of aromatics correlated with the fuel.